Novel Silver-Polymer Blend with High Conductivity and Stretchability for Flexible Interconnects. Issue 51 (17th June 2016) - Vanjaria, Jignesh; Houghton, Todd; Yu, Hongbin
ABSTRACT: Stretchable and flexible electronic devices have gained significant attention in recent years, as they can be integrated into many systems such as medical sensors, displays, and robots. One of the primary areas of research is designing stretchable interconnects which provide adequate conductivity and mechanical robustness. Metal-based interconnects have been reported to have the highest conductivity, but are not stretchable enough, while elastomer interconnects are not conductive enough. In this paper we report on a silver polymer blend composite that provides excellent conductivity, stretchability and flexibility for use as a stretchable interconnect. The composite was prepared by dispersing silver flakes in a Polyvinyl alcohol (PVA), Phosphoric acid (H3 PO4 ) and poly(3, 4-ethyl-ene-dioxythiophene) (PEDOT):Poly(styrene sulfonic acid) (PSS) polymer mixture. Silver was chosen as it has the highest conductivity of all metals, while the PEDOT:PSS/PVA- H3 PO4 blend was chosen as the blend offers a practical trade-off between conductivity and stretchability for the composite matrix. The polymer blend provides conductive pathways between the silver flakes, leading to the blend's superior electrical properties, even at large deformations. The synthesis process of the composite material, along with the observed electrical and mechanical properties under various straining conditions of the composite will be presented in detail.